HUBUNGAN ANTARA PERSEPSI TERHADAP SISTEMREWARD DAN PUNISHMENT DENGAN INTEGRITAS PEGAWAI STUDI KASUS : DINAS PENATAAN RUANG DAN PERMUKIMAN PROVINSI SUMATERA UTARA - DAMANIK, HANNA MEILANI (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2014)
Qualified human resources is a dominant factor for the implementation of good governance, one of which comes from the presence of the Civil Service of the highest integrity. In an effort to improve the integrity of the civil servants , the government has taken various steps which are perfect the system of rewards and punishment . The application of this system is reflected through various instruments such as the provision of benefits ( rewards ) and sanctions (punishment ) . Effective implementation of reward and punishment system is influenced by employee perceptions of the implementation of the system . The main impact is expected from the implementation of reward and punishment system is the formation of employee integrity in performing their duties.Formulation of the problem in this study is whether the employee s perception of the reward and punishment system is significantly related to the integrity of Sumatra Tarukim Service employee in performing their duties. This study aims to determine the relationship of perception of the civil service system of rewards and punishment to the integrity of Sumatra Tarukim Service employee in performing their duties. This research was conducted at the Department of Spatial Planning and Settlement of North Sumatra Province with a sample of 85 employees . Data were collected through questionnaires .Methods of data analysis performed by linear analysis with the help of SPSS software version 18. The analysis showed that the perception of reward and punishment system and the positive effect that was significant to the integrity of the officials in the Department of Spatial Planning and Settlement of North Sumatra Province